Design of Adhesive Hemostatic Hydrogels Guided by the Interfacial Interactions with Tissue Surface. Issue 2 (22nd December 2022) - Zhang, Xiaobin; Shi, Lianxin; Xiao, Wuyi; Wang, Zhao; Wang, Shutao
Abstract : Adhesive hemostatic hydrogels, as one of the most important wound dressings, have attracted tremendous attention because of their unique advantages in injured tissue. Many intensive efforts are devoted to designing ingenious adhesive hemostatic hydrogels based on interfacial interactions with tissue surfaces, such as covalent bonds, hydrogen bonds, electrostatic interactions, cation–π interactions, and π–π stacking interactions. Herein, an overview of the recent progress in adhesive hemostatic hydrogels is provided, especially focusing on diverse covalent/noncovalent interfacial interactions between the active groups of adhesive hydrogels and tissue surface. The commonly used forms and the hemostatic evaluation models of the adhesive hydrogels are also summarized. Finally, the critical issues that should be concerned for current adhesive hemostatic hydrogels and the developing directions toward practical applications are discussed. Abstract : Proper interfacial interactions between adhesive hydrogels and tissue surface are prerequisites for controlling bleeding. Herein, an overview of typical types of interfacial interactions between adhesive hydrogels and tissue is introduced, including covalent bonds, hydrogen bonds, electrostatic interactions, cation–π interactions, and π–π stacking interactions. The common forms and hemostatic evaluation models are also summarized.